EVALUASI POTENSI EKOWISATA DI TAHURA WAN ABDUL RACHMAN PROPINSI LAMPUNG - Gunardi Djoko Winarno; Tutut Sunarminto; Ricky Avenzora (Media Konservasi, 2011)
The Wan Abdul Rahman Provincial Park (Tahura Wan Abdul Rahman) is a well-known destination for many recreation and ecotourism activities amongst student in Lampung Province, but up to now the general function of the park is not reached yet. Therefore, an evaluation of ecotourism resources in the park have been held to find out the resources potential clearly, as well as to find it problems in management. The research shows that the water-fall, natural scenic and many floras and faunas in the park are very potential to suplly many recreation and ecotourism activities for a wide range of visitors; both for daily and week end recreation activities and for vacancies season. The Amorphophalus sp.  is the most uniqueness flora in this area and also world widely well known, while  the Burung Rangkong (Bucerotidae) is the most uniqueness fauna here. Further, the youth camp in this area is the most favorable focal point visited by the visitors. Keywords:  provincial park, ecotourism resource,  evaluation,  Amorphophalus sp., bucerotidae.